Penerapan Model Pembelajaran Children Learning In Science (Clis) Dalam Pembelajaran Pendidikan Kewarganegaraan Pada Materi Faktor Pendorong Dan Penghambat Persatuan Dan Kesatuan Bangsa Bagi Siswa Kelas Xi Ips Di Ma Darul Ihsan Samarinda - Rovik Rovik; Asnar Asnar; Wingkolatin Wingkolatin; Jawatir Pardosi; Suryaningsih Suryaningsih; Novita Majid (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to find out how the Application of Children Learning In Science (CLIS) Learning Model in Civic Education Learning on the Material of Encouraging and Inhibiting Factors of National Unity and Unity for Students of Class XI IPS at MA Darul Ihsan Samarinda. This research uses descriptive qualitative research. The research subjects were the Principal, Civics Teacher, homeroom teacher, and students of MA Darul Ihsan Samarinda. Data collection techniques using observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman model. Data validity using data triangulation. The results showed that the application of the learning model (CLIS) in learning civic education was well received by teachers and students, with a percentage of 61.22% agreeing from 20 respondents as reinforcement, besides that it made students able to argue and made learning less boring. In learning civic education, there are supporting factors including the availability of facilities and infrastructure and also adequate teaching staff, besides that, there are inhibiting factors including the unavailability of facilities and infrastructure such as LCDs that are not yet available in several classes so that it takes time to prepare for learning. This can make learning hours wasted. Efforts that must be made by the school to overcome problems in the learning process are to improve skills and complete school facilities.